Menakar Konstitusionalitas sebuah Kebijakan Hukum Terbuka dalam Pengujian Undang-Undang - Wibowo, Mardian (Mahkamah Konstitusi Republik Indonesia, 2015)
This study attempts to elaborate the definition of the â€œopen legal policyâ€ concept which has stated by the Constitutional Court as the autonomy of the Law- making body whenever UUD 1945 as the constitution did not regulate particular substances of a Law that is being made. In order to prevent this autonomy leans toward arbitrariness, it is necessary to establish a model of review towards open legal policies. One feasable option that the Constitutional Court could adapt is the